PENGEMBANGAN ELECTRONIC COMIC (E-COMIC) SEBAGAI BAHAN AJAR SUMPLEMEN MATERI EVOLUSI DI SMA NEGERI 1 DONOROJO - Verdayanti, Wanda; Kusumaningrum, Serafica Btari Christiyani; Prajoko, Setiyo (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
This study aims to determine the feasibility of e-comics on evolution material as supplementary teaching materials in biology learning and to determine the effectiveness of e-comics on evolution material as supplementary teaching materials in biology learning based on teacher and student responses. The type of this research is Research and Development (R&D) using the ADDIE model. The stages carried out in this study are: Analysis, namely analyzing the needs of teaching materials, curriculum, and materials; Design, namely consisting of a product creation schedule, product development team, product specifications, and product design; Development, namely developing e-comics and expert validation; Implementation, namely conducting teacher and student response tests; and Evaluation, namely analyzing the results at each stage of the research. The results of the study indicate that e-comic as a supplementary teaching material for evolution material is feasible to use. The e-comic's feasibility is stated based on the validation results of material experts, media experts, and teacher response tests, with percentage scores of 80.74%, 76.15%, and 82.63%. In addition, e-comic is also declared effective as a supplementary teaching material for evolution material based on the results of student response tests with a percentage score of 78.17%. Based on the analysis of product validation by material experts, media experts, and teacher response tests, e-comic is declared feasible to use as a supplementary teaching material for evolution material. Furthermore, the results of the student response test obtained indicate that e-comic is effective to use as a supplementary teaching material for evolution materia.l Keywords: E-Comic, Evolution Material, Supplementary Teaching Material